A Loading Dose of IV Salbutamol in an Adolescent with Severe Acute Asthma and Cardiac Arrest - Shelley A. Boeschoten; Ruben S. van der Crabben; Annemie L. M. Boehmer; Matthijs de Hoog; Corinne M. P. Buysse (Case Reports in Pediatrics)
Severe acute asthma (SAA) can lead to respiratory failure and can be fatal. For rational use of intravenous (IV) bronchodilators, evidence regarding the pharmacokinetics and pharmacodynamics is lacking in children. The use of a loading dose IV salbutamol is not mentioned in any international guideline, and its use varies greatly between PICUs worldwide. We describe a 17-year-old Caucasian female with SAA resulting in an out-of-hospital cardiac arrest. After basic life support and return of spontaneous circulation, the ambulance administered oxygen, inhaled salbutamol, IV magnesium sulphate, and systemic corticosteroids. Despite of this, she was still in severe respiratory distress. Therefore, a loading dose of IV salbutamol was administered, after which an immediate improvement was observed. Having a loading dose of IV salbutamol available for emergency medical services use for SAA in children with life-threatening SAA in the out-of-hospital setting is important to consider. Further study on the dose and the effect of a loading dose IV salbutamol in children with SAA is necessary.